Secondhand China Spain, the East, and the Politics of Translation. - PRADO-FONTS, CARLES (Book collections on Project MUSE., 2022)
"This book brings to light the ways Spanish writers relied on English- and French-language sources to imagine China and how this dependence on translation created the illusion of a homogeneous West"--